Hematopoietic Stem Cell Transplantation in Late‐Onset Krabbe Disease: No Evidence of Worsening Demyelination and Axonal Loss 4 Years Post‐allograft. Issue 3 (26th February 2018) - Laule, Cornelia; Vavasour, Irene M.; Shahinfard, Elham; Mädler, Burkhard; Zhang, Jing; Li, David K. B.; MacKay, Alex L.; Sirrs, Sandra M.
ABSTRACT: BACKGROUND AND PURPOSE: Late‐onset adult Krabbe disease is a very rare demyelinating leukodystrophy, affecting less than 1 in a million people. Hematopoietic stem cell transplantation (HSCT) strategies can stop the accumulation of toxic metabolites that damage myelin‐producing cells. We used quantitative advanced imaging metrics to longitudinally assess the impact of HSCT on brain abnormalities in adult‐onset Krabbe disease. METHODS: A 42‐year‐old female with late‐onset Krabbe disease and an age/sex‐matched healthy control underwent annual 3T MRI (baseline was immediately prior to HSCT for the Krabbe subject). Imaging included conventional scans, myelin water imaging, diffusion tensor imaging, and magnetic resonance spectroscopy. RESULTS: Brain abnormalities far beyond those visible on conventional imaging were detected, suggesting a global pathological process occurs in Krabbe disease with adult‐onset etiology, with myelin being more affected than axons, and evidence of wide‐spread gliosis. After HSCT, our patient showed clinical stability in all measures, as well as improvement in gait, dysarthria, and pseudobulbar affect at 7.5 years post‐transplant. No MRI evidence of worsening demyelination and axonal loss was observed up to 4 years post‐allograft. CONCLUSIONS: Clinical evidence and stability of advanced MR measures related to myelin and axons supports HSCT as an effective treatment strategy for stopping progression associated with late‐onset Krabbe disease.